PENGARUH CUSTOMER RELATIONSHIP MANAGEMENT (CRM) DAN TRUST TERHADAP LOYALITAS PELANGGAN PADA PT. KIKI EXPRESS RATU INTAN PERMATA - riska safitriani; Agustina Mutia; G.W.I. Awal Habibah (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
Customers are a valuable asset for every company, because they not only provide direct income through purchasing products or services, but can also be a source of positive references that help in improving the company's reputation. The aim of this research is to find out how partially or simultaneously customer relationship management and trust affect customer loyalty. In this research, researchers used the Quantitative Descriptive method. The technique used in sampling is the Isaac and Michael formula. Isaac and Michael's formula has provided useful calculation results for determining the number of samples based on an error rate of 1%, 5% and 10%. In this study the level of error or sampling error in the form of determining the number of samples is at the 10% level with a sample of 62 respondents. To collect data using questionnaires, interviews and documentation. The analysis techniques used are Data Quality Test, Classic Assumption Test, Hypothesis Test, Multiple Linear Regression Analysis and Coefficient of Determination. The research results show that: customer relationship management (CRM) (X1) has a significant effect on customer loyalty. Trust (X2) has no significant effect on customer loyalty. customer relationship management (CRM) (X1) and trust (X2) simultaneously have a significant effect on customer loyalty (Y).